The Resource Curse: The Situation of Women in Resource-Rich Countries - Domagała, Wiktoria; Dymitrowska, Yanina (Ekonomia i Prawo. Economics and Law, 2025)
This research was supported by funds granted by the Minister of Science of the Republic of Poland under the „Regional Initiative for Excellence” Programme for the implementation of the project“The Poznań University of Economics and Business for Economy 5.0: Regional Initiative – Global Effects (RIGE)”. Motivation: The occurrence of the resource curse phenomenon presents a significant challenge to the long-term, stable, and sustainable economic development of resource-rich countries. The paradox is a multidimensional phenomenon, encompassing economic, political, and social dimensions. An important issue that has been receiving increasing attention from researchers in recent years is determining the impact of natural resource abundance on women’s economic and political participation. Aim: This study aims to assess the situation of women in the professional sphere in countries rich in natural resources. Results: The study conducted a detailed analysis of the situation of women in the professional sphere of 46 resource-rich countries over the period 1990–2020. It employed a critical literature review and quantitative methods, including data mining techniques such as cluster analysis and descriptive statistics. Based on the results of the study, it was found that in countries rich in natural resources where Islam is practiced, the situation of women in the professional sphere, considering all analysed indicators, is worse. The significant impact of Islam on the situation of women in resource-rich countries is additionally confirmed by the results obtained for the United Arab Emirates, which were classified among highly developed countries that achieve positive development outcomes in the context of the resource curse. However, the situation of women in this country is just as unfavourable as in the group of predominantly Islamic states. Thus, Islam significantly affects the situation of women in the professional sphere in resource-rich countries. Moreover, economies that are more heavily dependent on natural resource revenues tend to exhibit deeper gender disparities across key dimensions of labour market participation. The best results regarding the situation of women are achieved by developed countries that have managed to avoid the effects of the resource curse.